2018
DOI: 10.1089/jwh.2017.6791
|View full text |Cite
|
Sign up to set email alerts
|

Linking Education to Action: A Program to Increase Research Participation Among African American Women

Abstract: An online education-to-action program targeting professional African American women improved knowledge, perceptions of ethics, and intent to participate in biomedical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It is well documented that NHB women are more likely to be diagnosed with TNBC and are most likely to die from breast cancer compared to all other ethnic groups 2,4,12,15,16 . However, NHB women are underrepresented in breast cancer research studies 17,18 , including studies investigating the breast microbiome. Our study is the first to show differences in the breast tissue microbiota between NHB and NHW women.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that NHB women are more likely to be diagnosed with TNBC and are most likely to die from breast cancer compared to all other ethnic groups 2,4,12,15,16 . However, NHB women are underrepresented in breast cancer research studies 17,18 , including studies investigating the breast microbiome. Our study is the first to show differences in the breast tissue microbiota between NHB and NHW women.…”
Section: Discussionmentioning
confidence: 99%
“…However, CBA focus on broad methods for recruitment and less on message content. Existing studies also have reported on the use of educational materials and seminars to improve African American recruitment (Skinner et al, 2008; Halverson and Ross, 2012; Rodriguez et al, 2016; Radecki Breitkopf et al, 2018). Studies found pre-post increases in knowledge about genomic studies, more favorable attitudes (Patel et al, 2018) and less negative affect (Kiviniemi et al, 2013) after receiving an educational intervention.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Despite this underrepresentation, previous studies have shown that AAs have an interest to participate in a variety of medical research studies beyond traditional clinical trials including medical record review, interview, and biobank/genetic studies. 5 , 6 The failure to create a more racially diverse research cohort perpetuates existing health and healthcare disparities which disproportionately affect AAs.…”
Section: Introductionmentioning
confidence: 99%